PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI DI PASAR MODAL PADA ANGGOTA UKM KSPM UNIVERSITAS JAMBI - Alif Faturrahman; Dr. Ida Masriani, S.E., M.M.; Dr. Moh. Ihsan, S.E., M.Si. (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of financial literacy on investment decisions among members of the Capital Market Study Group (KSPM) at Universitas Jambi. Investment decisions are categorized into three dimensions: rational, intuitive, and dependent. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), analyzed through SmartPLS 4 software. The sample consisted of 88 active KSPM UNJA members. The results show that financial literacy has a positive and significant effect on rational investment decisions, a negative and significant effect on dependent investment decisions, and a negative but insignificant effect on intuitive investment decisions. These findings indicate that individuals with higher financial literacy are more likely to make logical, analytical decisions and are less influenced by intuition or others' opinions. The implications of this study highlight the importance of enhancing financial literacy among university students, especially those involved in capital market activities, to foster more responsible, independent, and well-informed investment behavior.